Measuring Investment in Learning: Can Electrocardiogram Provide an Indication of Cognitive Effort During Learning?. Issue 2 (April 2016) - Patterson, Jae T.; Hart, Amanda; Hansen, Steve; Carter, Michael J.; Ditor, David
Heart rate variability (i.e., low frequency:high frequency ratio) was measured to differentiate invested cognitive effort during the acquisition and retention of a novel task. Participants (12 male, M = 25.1 year, SD = 3.6; 12 female, M = 22.8 year, SD = 1.1) were required to produce Braille equivalents of English letter primes on a standardized keyboard in proactive or retroactive conditions (groups, each n = 12). The correct Braille response was either provided before (i.e., proactively) or after (i.e., retroactively) the participant's response. During acquisition, participants in the proactive group demonstrated shorter study time, greater recall success, and reported lower cognitive investment. Participants in the proactive and retroactive groups did not statistically differ in heart rate variability. For retention, the retroactive group showed greater recall success, lower perceived cognitive effort investment, and lower heart rate variability. The results highlight the usefulness of heart rate variability in discriminating the cognitive effort invested for a recently acquired skill.